PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY UNTUK MENINGKATKAN PEMAHAMAN KONSEP IPA SISWA SMP PADA MATERI POKOK ZAT DAN WUJUDNYA - Syuryadi, Yelleson (Edu Research, 2014)
Result which obtained in this research that is: ( 1) understanding of IPA concept Class student of VII.2 SMP Negeri 1 Rambah by using model study of type cooperative of Two Stay Two Stray in general pertained is, posed at by finding at cycle of I only 53,13% from 32 student which have fulfilled complete standard learn to minimize (SKBM) with value of lowest equal to 47, highest value 87, and also average value equal to 65,42, and standard of deviation 12,26. While at cycle of II tired 84,38 % from 32 student which have fulfilled SKBM, with value of lowest equal to 50, highest value equal to 88, and also average value equal to 74,02 and standard ofdeviation 7.63.